2021
DOI: 10.1039/d1nr02363b
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmonic resonance tunable nanocomposite thin films applicable to color filters, heat mirrors, semi-transparent electrodes, and electromagnetic-shields

Abstract: This study proposes a plasmonic resonance tunable nanocomposite thin film which is applicable to color filter, heat mirror, semi-transparent color electrode, and electromagnetic-shield, given the size and structure of nanoclusters...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The tuning of plasmon resonances has important applications in biosensor devices and photovoltaics , because the plasmon resonance strongly depends on the cluster size, arrangement, the materials used, and their composition . Especially the use of bimetallic alloys allows for fine-tuning of the plasmon resonance, which offers new pathways in anticounterfeiting: in combination with polymer supports and templates, structural color can readily be achieved by exploiting the plasmon resonance. , Moreover, this enables fast electrochromic color switching of smart windows . Hence, understanding the correlation of size and composition with the plasmonic and optoelectronic behavior of polymer-supported metal cluster systems carries high potential but also is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The tuning of plasmon resonances has important applications in biosensor devices and photovoltaics , because the plasmon resonance strongly depends on the cluster size, arrangement, the materials used, and their composition . Especially the use of bimetallic alloys allows for fine-tuning of the plasmon resonance, which offers new pathways in anticounterfeiting: in combination with polymer supports and templates, structural color can readily be achieved by exploiting the plasmon resonance. , Moreover, this enables fast electrochromic color switching of smart windows . Hence, understanding the correlation of size and composition with the plasmonic and optoelectronic behavior of polymer-supported metal cluster systems carries high potential but also is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The TF-SiO x 60/PPFC developed in this study is one of the best of all papers reported for using Si-based anodes in terms of cycle life and capacity retention. The fabrication method using these mixed targets had the advantage of depositing various materials (Cu, [33] Ag, [34] and ZnO [35] ), suggesting that high-quality thinfilms for TF-LIBs can be deposited using materials other than SiO x . Figure 5d schematically shows the operating mechanism for the proposed TF-SiO x 60/PPFC TF-SiO x 100 thin-films based on the above results and discussions.…”
Section: Resultsmentioning
confidence: 99%
“…In the high-resolution XPS spectra for the IL-1β-templated PEBT film on the 4-AMP/PEDOT/SPCE, the strong C 1s peaks detected in the MIP film after the IL-1β extraction indicate four major components, which are attributed to different carbon atoms within the polymer matrix (Figures 3b and S13a). Specifically, as shown in Figure 2d, each component in the chemical bonding group separately reveals O=C-O (288.2 eV), O=C-N/C=N (287 eV), C-N/C-O (286.5 eV), and C-C (284.8 eV) [79,80]. In contrast, the C 1s spectra of the MIP/4-AM/PEDOT/SPCE represent similar chemical features of the individual components compared with the PEDOT/SPCE and 4-AMP/PEDOT/SPCE (Figure S13a).…”
Section: Surface Characterization Of Pebt-based Mip Filmsmentioning
confidence: 96%